Perivascular adipose tissue inhibits endothelial function of rat aortas via caveolin-1. - Michelle Hui-Hsin Lee (PLoS ONE, 2014)
Perivascular adipose tissue (PVAT)-derived factors have been proposed to play an important role in the pathogenesis of atherosclerosis. Caveolin-1 (Cav-1), occupying the calcium/calmodulin binding site of endothelial NO synthase (eNOS) and then inhibiting nitric oxide (NO) production, is also involved in the development of atherosclerosis. Thus, we investigated whether PVAT regulated vascular tone via Cav-1 and/or endothelial NO pathways. Isometric tension studies were carried out in isolated thoracic aortas from Wistar rats in the presence and absence of PVAT. Concentration-response curves of phenylephrine, acetylcholine, and sodium nitroprusside were illustrated to examine the vascular reactivity and endothelial function. The protein expressions of eNOS and Cav-1 were also examined in aortic homogenates. Our results demonstrated that PVAT significantly enhanced vasoconstriction and inhibited vasodilatation via endothelium-dependent mechanism. The aortic NO production was diminished after PVAT treatment, whereas protein expression and activity of eNOS were not significantly affected. In addition, Cav-1 protein expression was significantly increased in aortas with PVAT transfer. Furthermore, a caveolae depleter methyl-β-cyclodextrin abolished the effect of PVAT on the enhancement of vasoconstriction, and reversed the impairment of aortic NO production. In conclusion, unknown factor(s) released from PVAT may inhibit endothelial NO production and induce vasocontraction via an increase of Cav-1 protein expression.